2019
DOI: 10.31235/osf.io/89gcu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of housing on family size in South Korea: Unstable housing and parity specific risk

Abstract: Increasing housing cost is one of the major concerns among young parents in South Korea. The aim of this study is to evaluate how homeownership is associated with parity-specific birth. We use the 2009-2017 waves of the Korea Labor and Income Panel Study (n=6,934) to illustrate opt-out childbearing without the state of being a homeowner. This study uses the Cox proportional hazard model to show mutually-exclusive patterns between homeownership and childbearing. The results suggest that either short-term rent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Worries about the future go beyond the economic fallout from the 2008 recession while including xenophobic responses to the refugee crisis in 2015. Euroscepticism, the rise of populism and Russia's war of aggression against Ukraine, all contribute to spreading a feeling of uncertainty and unpredictability that prospective parents are faced with when deciding whether to have a(nother) child (Comolli et al, 2021[54]; Joris, Puustinen and d'Haenens, 2018 [83]; Vignoli et al, 2020[78]). Furthermore, Dillarstone et al (2023 [84]) found that climate change concerns were typically associated with less positive attitudes towards reproduction and a desire and/or intent for fewer children or none at all -their systematic review was based on studies conducted between 2012 and 2022 in European countries, Canada, New Zealand and the United States.…”
Section: Perceived and Anticipated Uncertainties Mattermentioning
confidence: 99%
“…Worries about the future go beyond the economic fallout from the 2008 recession while including xenophobic responses to the refugee crisis in 2015. Euroscepticism, the rise of populism and Russia's war of aggression against Ukraine, all contribute to spreading a feeling of uncertainty and unpredictability that prospective parents are faced with when deciding whether to have a(nother) child (Comolli et al, 2021[54]; Joris, Puustinen and d'Haenens, 2018 [83]; Vignoli et al, 2020[78]). Furthermore, Dillarstone et al (2023 [84]) found that climate change concerns were typically associated with less positive attitudes towards reproduction and a desire and/or intent for fewer children or none at all -their systematic review was based on studies conducted between 2012 and 2022 in European countries, Canada, New Zealand and the United States.…”
Section: Perceived and Anticipated Uncertainties Mattermentioning
confidence: 99%